Experimental characterization and theoretical prediction of quasi‐static fracture behavior of notched ZK60‐T5 Mg samples. Issue 6 (7th March 2021) - Albinmousa, Jafar; Peron, Mirco; Razavi, Seyed Mohammad Javad; Al Hussain, Mohammed; Al‐Ghanim, Ahmed; Berto, Filippo
Abstract: Magnesium and its alloys have increasingly gained attention due to their attractive properties, including the high specific strength that makes them suitable for several applications in different industries. However, their applications in load‐bearing components require an understanding of their fracture behavior especially when notches are present which is still limited. The aim of this work is to investigate the fracture behavior of notched ZK60‐T5 magnesium. Eleven different U‐ and V‐notched geometries were examined. The mechanical tests showed that the presence of notches reduces the ductility of the material. This was confirmed by the SEM as the size of the shear lips was shown to decrease by increasing the notch acuity. The Strain Energy Density (SED) is used to predict the failure loads of the differently notched samples, and the results suggest high reliability of this approach with deviations between the theoretical and experimental data often lower than 10%.